Peningkatan konduktivitas termal lemak sapi sebagai bahan PCM dengan menambahkan arang sekam padi - I.M. Astika; I.N.S. Winaya; I.D.G.A. Subagia; I.K.G. Wirawan; I.G.K. Dwijana; I.G.K. Sukadana (Dinamika Teknik Mesin, 2021)
Phase change material (PCM) is a material that can absorb and store energy and can release it based on the principle of latent heat energy storage. Beef tallow is one of the materials that can be used as PCM but its low thermal conductivity is around 0.181 W/mK. Hence, thermal conductivity is considered an important factor in the conduction heat transfer.  This further affects kinetic absorption and heat release. However it is possible to increase the values by adding another material that has a high thermal conductivity. The purpose of this study is to elevate the thermal conductivity of beef tallow by adding rice husk char. This research involves direct incorporation method, where beef tallow is thawed and mixed with the rice husk char then stirred with a rotation of 100 rpm until the mixture becomes solid. Addition of rice husk char with weight fractions of 5 and 10% and grain size of 0.045 mm. Subsequently, thermal conductivity test was performed using the TQ Heat Transfer Experiment Base Unit.The results show that with the addition of rice husk can increase the thermal conductivity of PCM beef tallow. The increase obtained in the addition of 10% rice husk char is 37 times compared to the pure sample. Based on this result it is concluded that carbon-based materials such as rice husk char can be used to increase the thermal conductivity of PCM materials.